2022
DOI: 10.47616/jamrmhss.v3i4.346
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Ethyl Acetate Extract of Sungkai Leaves (Peronema Canescens Jack.) Against Blood Glucose Levels in Alloxan-Induced Male Mice

Abstract: This research aims to test antidiabetic using alloxan induction on mice test animals. The type of research used is experimental, which includes sampling, sample determination. Extract preparation with ethyl acetate solvent, extract characteristics test and simplicia, extract and simplicia screening test. Antidiabetic testing was carried out using male mice as test animals. Screening tests for the presence of alkaloids, flavonoids, tannins, saponins, steroids, and glycosides for the anti-diabetic test of Sungka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The leaves and roots of sungkai have also long been used as traditional medicine in the Dayak Tunjung tribe as a medicine for fever, diuretic and rheumatic pain, and the Lembak Empat tribe in Bengkulu still uses the young leaves of sungkai to maintain health, treat high fever and malaria [1]. Currently, sungkai research focuses on leaves as an extract which has potential as an antipyretic [2] anti-inflammatory [3,4], antioxidant [5][6][7][8], antibacterial [9][10][11], Antihyperuricemia [12], anticancer [13,14], and antidiabetic [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The leaves and roots of sungkai have also long been used as traditional medicine in the Dayak Tunjung tribe as a medicine for fever, diuretic and rheumatic pain, and the Lembak Empat tribe in Bengkulu still uses the young leaves of sungkai to maintain health, treat high fever and malaria [1]. Currently, sungkai research focuses on leaves as an extract which has potential as an antipyretic [2] anti-inflammatory [3,4], antioxidant [5][6][7][8], antibacterial [9][10][11], Antihyperuricemia [12], anticancer [13,14], and antidiabetic [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the phytochemical test on Sungkai revealed that the plant contains various secondary metabolites, including alkaloids, steroids, terpenoids, tannins, and saponins. 6 Another research shows that the ethanol extract of sungkai leaf also contains phenolics, anthraquinones, and flavonoids. Flavonoids are polyphenols found in many plants.…”
Section: Introductionmentioning
confidence: 99%